Traditional Chinese medicine for diabetic peripheral neuropathy: a network meta-analysis - Hu, Jinglin; Wang, Haili; Hao, Xiaogang; Pan, Ting; Li, Xuefeng; Zhou, Xue; Wang, Siyi; Gong, Yubo; Wu, Lingfeng; Dong, Shuo; Chen, Xinhua; Wang, Xichen (Frontiers in Endocrinology, 2025)
BackgroundDiabetic peripheral neuropathy (DPN) is a common complication of diabetes mellitus, characterized by high morbidity and significant disability. Traditional Chinese medicine (TCM) has shown potential in relieving symptoms and improving neurological function through multi-targeted mechanisms; however, the efficacy and safety of different TCM therapies have yet to be systematically evaluated.ObjectiveThis study aims to provide evidence-based medicine for treating DPN with TCM therapy by network meta-analysis (NMA).MethodsThis study comprehensively searched nine databases constructed up to November 2024. The quality and evidence of the included RCTs were assessed using the risk of bias assessment tool and GRADE pro, and pairwise meta-analysis and NMA were performed using RevMan, Stata, and R Studio. The results showed that 95 RCTs involving 8194 patients were included, containing 9 TCM therapies.ResultsTCM Decoration + Acupuncture ranked highest in improving the motor conduction velocity of the common peroneal nerve (SUCRA = 0.81), followed by TCM Decoction + Chinese Herbal Footbath (SUCRA = 0.80), electroacupuncture (SUCRA = 0.75). Regarding the sensory conduction velocity of the common peroneal nerve, TCM Decoration + Chinese Herbal Foot (SUCRA=0.87) ranked first, followed by TCM Decoction + Acupuncture (SUCRA = 0.83), and TCM Decoction (SUCRA = 0.51). Electroacupuncture (SUCRA = 0.83) ranks first in improving median nerve motor conduction velocity, followed by TCM Decoction + Acupuncture (SCURA = 0.98), TCM Decoction (SUCRA = 0.55). TCM Decoration + Acupuncture (SUCRA=0.98) ranks first in improving the sensory conduction velocity of the median nerve, followed by electroacupuncture (SUCRA = 0.51), and Chinese Patent Medicine (SUCRA = 0.51). TCM Decoration + Chinese Herbal Footbath (SUCRA = 0.85) ranked first in improving overall clinical symptoms of DPN.ConclusionThe effectiveness and safety of traditional Chinese medicine therapy in treating DPN have been preliminarily verified. In clinical practice, conservative clinical stratification selection can be made based on the results of this study and the actual situation. In addition, due to the limited quality of the included studies, larger sample sizes and high-quality research are still needed.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier (CRD42024589159).